The module of natural language commands reception - Сич, М. Ю. (Problems of Informatization and Control, 2008)
Described common structure and work concepts of the module of natural language commands reception – one of the most modern interaction types between human and computer systems. There are described module main functioning rules commonly, and its parts. There is description of algorithm for searching semantic connections between words, structure of library allowed commands